Accumulation of deleterious mutations in the domestic yak genome. (30th July 2018) - Xie, X.; Yang, Y.; Ren, Q.; Ding, X.; Bao, P.; Yan, B.; Yan, X.; Han, J.; Yan, P.; Qiu, Q.
Summary: Deleterious mutations play an important functional role, affecting trait phenotypes in ways that decrease the fitness of organisms. Estimating the frequency of occurrence and abundance has been a topic of much interest, especially in crops and livestock. The processes of domestication and breeding allow deleterious mutations to persist at high frequency, and identifying such deleterious mutations is particularly important for breed improvement. Here, we assessed genome‐wide patterns of deleterious variation in 59 domestic and 13 wild yaks using genome resequencing data. Based on the intersection of results given by three methods (provean, polyphen 2 andsift 4g ), we identified 3187 putative deleterious mutation sites affecting 2586 genes in domestic yaks and 2067 affecting 1701 genes in wild yaks. Multiple lines of evidence indicate a significant increase in the load of deleterious mutations in domesticated yaks compared to wild yaks. Private deleterious genes were found to be associated with the perception of smell and detection of chemical stimulus. We also identified 36 genes related to Mendelian genetic diseases involved in sensory perception, skeletal development and the nervous and immune systems. This study not only adds to the understanding of the genetic basis of yak domestication but also provides a rich catalog of variants that will facilitate future breeding‐related research on the yak genome and on other bovid species.